Organizational Readiness for Community Health Worker Workforce Integration Among Medicaid Contracted Health Plans and Provider Networks: An Arizona Case Study - Sabo, Samantha; Wexler, Nancy; O'Meara, Louisa; Dreifuss, Heather; Soto, Yanitza; Redondo, Floribella; Carter, Heather; Guernsey de Zapien, Jill; Ingram, Maia (Frontiers in Public Health, 2021)
Understanding and building organizational capacity for system change and the integration of the Community Health Worker (CHW) workforce within the health scare sector requires a supportive organizational culture among sector leaders and providers. The aim of this mixed-methods study was to assess organizational readiness for CHW workforce integration into Arizona Medicaid health systems and care teams. To achieve this, we assessed the attitudes, beliefs, and values among 245 licensed health care providers from across a variety of health care contexts and among 16 leadership representatives of all Medicaid-contracted health plans in Arizona. Our findings demonstrate a high level of organizational readiness and action toward integration of CHWs within the Arizona health care system and care teams. CHWs have emerged as a health care workforce able to enhance the patient experience of care, improve population health, reduce cost of care, and improve the experience of providing care among clinicians and staff.